Sistem Informasi Penggajian Dan Absensi Pada Apotek Mulya Farma Kudus Berbasis Website - Wicaksono, Yoga Adi; Meimaharani, Rizkysari; Khotimah, Tutik (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Apotek Mulya Farma Kudus, like many other businesses, faces challenges in managing employee data, especially related to payroll and attendance. The manual process that is still applied often results in inaccurate data, is time consuming, and has the potential to cause calculation errors. To overcome these problems, this study aims to develop an integrated computer-based payroll and attendance information system. This system is expected to automate the process of recording attendance, calculating salaries, and producing accurate and fast reports. The system development method used is by referring to the relevant information system development methodology. The stages that are passed include needs analysis, system design, implementation, and testing. This system is built using the PHP programming language using the Codeigniter framework and the waterfall development method. The results of this study are an information system that is able to manage employee data effectively and efficiently. The features contained in the system include: online attendance recording, automatic salary calculation based on various salary components, making pay slips, and various reports required by management. With this information system, it is expected to increase efficiency and accuracy in managing employee data at Apotek Mulya Farma Kudus based on the website. In addition, this system can also reduce the potential for human error and provide more accurate information for decision making.